EFFEC OF THE ZINC ON THE SOME OF BLOOD PARAMETER AND SOME ORGANS IN LOCAL DUCK (ANAS PLATER HYCOUS) - Firas Ali Hussein (Basrah Journal of Veterinary Research)
This experiment was designed to elicit the effect of zinc on the hematological picture and the histological effect on heart, kidney and liver of the domestic ducks. The birds were divided into two groups of eight birds each. The first group was the control group and the second one was the treated group in which the birds were fed the zinc sulphate as 100 mg/kg with food for four weeks. The results showed a decrease in hemoglobin, MCV, MCH, and MCHC. And an increase in red blood cells blood cholesterol,GOT and GPT. Histologicaly, the results showed a hydropic degeneration in the myocardial and renal cells beside a fatty degeneration in the liver texture